Related Factors to BSE Practices in Female Undergraduate Students Aged 18-24 Years: A Cross-Sectional Study in Tembalang Subdistrict, Semarang City - Asriyanti, Anggi (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2023)
Introduction: Shifts in disease patterns are a double burden on world health, such as breast cancer in young women < 40 years old with an Age-Standardized Incidence Rate reaching 8.2 or 100,000 world population. Breast Self Examination (BSE) has a meaningful role in the initial detection of breast cancer, so it can prevent cancer from delayed detection and increase women's life expectancy as a risk group. BSE practice should have been routinely implemented at the age of female students. This research aims to determine related factors to BSE practices in female undergraduate students aged 18-24 in Tembalang Subdistrict.Methods: This observational analytic research uses a cross-sectional approach with female undergraduate students aged 18-24 years in Tembalang Subdistrict as a population. There were 200 samples with a 1:1 ratio of groups that do BSE and those that do not. This research used a questionnaire with online data collection via Google Forms, then imposed univariate and bivariate analysis with a chi-square test.Results: Family history of breast cancer (ρ=0.001), information exposure (ρ=0.000), and awareness (ρ=0.007) were related to BSE practice in female undergraduate students aged 18-24 years.Conclusion: It is essential to provide a valid source of information on social media as the most frequently used information exposure media about breast cancer and ways of initial detection, so every woman can have awareness, whether she has a family history of breast cancer or not.